The Donetsk's myth. Ontologi of the citys self-definition - Aleksandr Belokobylskiy; Kseniia Sidorova (Cхід, 2014)
One of the main trends of modern society is a marked increase of the theoretical interest to the sphere of mythology and the theory of myth. And in light of globalization approaches explicitly focus on the impact study of the regional aspects of social phenomena. In this regard, in regional studies of mythology appear attempts seen the myth city's as a socially formalized knowledge about the city or region, a strong regulatory and mobilization element in society, which is capable of forming a regional entity and identity.